1968
DOI: 10.1099/00221287-52-1-131
|View full text |Cite
|
Sign up to set email alerts
|

The Catabolism of Acyclic Polyols by Yeasts

Abstract: S U M M A R YEight polyols were employed in turn as sole carbon source for aerobic growth tests with sixteen yeasts. The yeasts studied varied from those using none to others using all the polyols. Mean generation times in aerated, liquid, shaken medium for five yeasts and four polyols, were from 2 to 7.5 hr.With seven yeasts, oxygen uptake was measured for different polyols as sole carbon source, of washed, starved yeast cells, harvested in the exponential phase of growth. No yeast respired a substrate on whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…cerevisiae for growth on mannitol Of the 40 polyploid strains of S. cereuisiae screened (Table l), 20 were capable of good growth (5-20mg dry wt ml-*) on 5 % mannitol. It may therefore be concluded that the generally held view that S. cereuisiae cannot grow on mannitol (Barnett, 1968;Spoerl & Doyle, 1968) mannitol (van der Walt, 1970). It is unfortunate that the methods used by taxonomists for the measurement of growth are semi-quantitative so that direct comparison with the work reported here cannot be made.…”
Section: Results a N D Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…cerevisiae for growth on mannitol Of the 40 polyploid strains of S. cereuisiae screened (Table l), 20 were capable of good growth (5-20mg dry wt ml-*) on 5 % mannitol. It may therefore be concluded that the generally held view that S. cereuisiae cannot grow on mannitol (Barnett, 1968;Spoerl & Doyle, 1968) mannitol (van der Walt, 1970). It is unfortunate that the methods used by taxonomists for the measurement of growth are semi-quantitative so that direct comparison with the work reported here cannot be made.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…cerevisiae (Wolff & Kaplan, 1956), neither being grown on mannitol. However, taxonomists have noted that some strains of S. cerevisiae can assimilate mannitol (van der Walt, 1970), although in a more recent text (Barnett et al, 1983) growth was reported either not to occur or to occur after a delay of 14-21 d. More specifically, growth of S. cerevisiae on mannitol has been suggested (Kirsop, 1974) or shown (Wiles, 1953;Quain, 1986) to be useful in the differentiation of brewing yeasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…$ 0n3. Each growth was measured at least four times at 640 nm and calibrated in terms of dry weight (Barnett, 1968). Doubling times were calculated from the linear relationship between the logarithm of dry weight and time, during exponential growth.…”
Section: Methodsmentioning
confidence: 99%
“…Each flask was inoculated with about I mg dry wt of yeast from a I-day-old YM agar slope, and was incubated in a Gallenkarnp Orbital shaker at 175rev./min. Growth was measured with a nephelometer, calibrated in terms of dry weight (Barnett, 1968) about every 10 h during growth. Each experiment was done at least twice.…”
mentioning
confidence: 99%